2020
DOI: 10.1097/ceh.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Training Interventions to Equip Health Care Professionals With Shared Decision-Making Skills: A Systematic Scoping Review

Abstract: Despite numerous initiatives to increase SDM worldwide, SDM has not yet been widely implemented in clinical practice. A key barrier to SDM is that many health professionals have not been trained with the relational and communication skills required for SDM. To support the development and implementation of SDM training programs, this paper maps the evidence in relation to SDM training programs for health professionals and students, in terms of training design and content as well as evaluation outcomes. Method:U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 81 publications
(374 reference statements)
3
18
0
Order By: Relevance
“…Few studies assessing shared decision making training programmes have evaluated the impact of training on participants' confidence and knowledge. 18 An 8-hour face-to-face training programme for physicians reported an increase in confidence and knowledge, but areas of knowledge assessed are not detailed. 19 Evaluation of a brief online single case-based approach for primary care clinicians reported a reasonable level of confidence in performing and high level of knowledge of shared decision making steps after completing the case, but levels were not measured prior to undertaking it.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies assessing shared decision making training programmes have evaluated the impact of training on participants' confidence and knowledge. 18 An 8-hour face-to-face training programme for physicians reported an increase in confidence and knowledge, but areas of knowledge assessed are not detailed. 19 Evaluation of a brief online single case-based approach for primary care clinicians reported a reasonable level of confidence in performing and high level of knowledge of shared decision making steps after completing the case, but levels were not measured prior to undertaking it.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…27 It is not clear whether this course included risk communication, and this component of training was particularly noted as lacking across all courses in the review of shared decision making training interventions by Coates and Clerke. 18 There are few online courses that have been evaluated or published results. Imagine that a new drug for osteoporosis has just been approved.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…To ensure that women make informed decisions about their own care, they should be provided with unbiased information about their birth options, informed by the evidence, and their own birth beliefs and preferences should be considered in the decision‐making process 49 . Clinicians may benefit from reflecting on their own beliefs and values and making them explicit to help ensure they do not inadvertently influence women toward their own birth preferences 50 . In addition, to help ensure women are provided with unbiased information, decision aids can be used to present women with the evidence in terms of risks and benefits of any intervention 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…50 A recent systematic review of 36 SDM interventions concluded that a wide range of multilevel avenues are feasible, however, more rigorous testing is still required to identify effective approaches. 51 Unanswered questions and future research Future studies may consider exploring the perspective of women of reproductive age with CIDs, as well as GPs and OB/GYNs. A larger sample size with a wider range of perspectives (eg, ethnicities) would ensure greater implications of results for the disease-affected population.…”
Section: Implications For Clinicians and Policymakersmentioning
confidence: 99%
“…53 Lastly, further research is required to evaluate the effectiveness of various SDM interventions. 51 CONCLUSION Dermatologists and rheumatologists experience knowledge, skill and confidence gaps in relation to childbearing, treatment and management discussions with women of reproductive age with CID. They also experience challenges collaborating with other healthcare providers involved in the care of these patients.…”
Section: Implications For Clinicians and Policymakersmentioning
confidence: 99%